2005
DOI: 10.1128/jcm.43.3.1408-1410.2005
|View full text |Cite
|
Sign up to set email alerts
|

Presence of DNA of Human Papillomavirus 16 but No Other Types in Tumor-Free Tonsillar Tissue

Abstract: According to PCR, the prevalences of human papillomavirus (HPV) DNA were 6.3% (13 of 206) in tonsillitis or hypertrophic tonsillar tissues and 0.6% (1 of 174) in exfoliated cells from normal tonsils. HPV-16 was the only type detected in tonsillar tissues, but it did not appear to lead to L1 antibody production.Of the squamous cell carcinomas of the head and neck, human papillomavirus (HPV) DNA has been repeatedly reported in tonsillar carcinoma, suggesting a role for HPV in tonsillar carcinogenesis (5,9,10,13,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 25 publications
7
45
0
4
Order By: Relevance
“…Biopsies of skin (n ϭ 54) were obtained from patients with B19-unrelated dermatological lesions and from healthy hospital or laboratory staff (range, 1913-1991; mean, 1951 Ϯ 19). Biopsies of tonsillar tissue (n ϭ 220) were obtained during tonsillectomy from patients (range, 1929-2000; mean, 1979 Ϯ 15) with tonsillitis or tonsillar hypertrophy (44).…”
Section: Methodsmentioning
confidence: 99%
“…Biopsies of skin (n ϭ 54) were obtained from patients with B19-unrelated dermatological lesions and from healthy hospital or laboratory staff (range, 1913-1991; mean, 1951 Ϯ 19). Biopsies of tonsillar tissue (n ϭ 220) were obtained during tonsillectomy from patients (range, 1929-2000; mean, 1979 Ϯ 15) with tonsillitis or tonsillar hypertrophy (44).…”
Section: Methodsmentioning
confidence: 99%
“…They found 9 of 106 tonsils to be HPV-positive, with six cases having HPV-16, two cases having HPV-11 and one case having an untyped HPV (Mammas et al, 2006). Another study reported HPV-16 infection in 13 of 206 tonsils (6.3%) with 11 cases from children or young adults aged less than 25 years (Chen et al, 2005). These findings differed from those of several other studies in which low prevalence or no prevalence of oncogenic and non-oncogenic HPV was identified in the specimens studied (Brandsma & Abramson, 1989;Klingenberg et al, 2010;Klussmann et al, 2001;Niedobitek et al, 1990;Ribeiro et al, 2006;Sisk et al, 2006;Snijders et al, 1992).…”
Section: Incidence Of Hpv In Normal Tonsilmentioning
confidence: 97%
“…[12,13]. Cependant, d'autre modes de transmission sont suspectés, comme le suggère la détection (PCR) de HPV oncogènes dans des pièces d'amygdalectomie chez les enfants [14,15].…”
Section: Hpv Et Cancers Des Vads : Mécanismes Oncogéniquesunclassified